Analisis Pelaksanaan Program Keselamatan Pasien IGD di RS Vina Estetika Medan - Zebua, Arianus; Bangun, Herianto (Universitas Malahayati, 2024)
ABSTRACT Patient safety is defined as a service that aims not to injure and harm patients or as a system in which hospitals make patient care safer. The target of compliance with patient identification correctly, effective communication with SBAR procedures, compliance by officers in maintaining hand hygiene, and compliance with identification of patients at risk of falling are still below 100%. The purpose of this study is to analyze the Implementation of the Emergency Room Patient Safety Program at the Vina Aesthetic Hospital Medan in 2021. This type of research is using descriptive descriptive with naturalistic nature. The data obtained through interviews with several main informants and additional informants, namely ER patients with the Triangulation method, can be concluded: Input (HR, every nurse or implementer in the ER has carried out patient safety well), Process (Patient Safety has been carried out in accordance with SOPs by applying maximum patient identification), Output (ER patient, feels that the identification has been carried out properly). The conclusion in this study is that the implementation of patient safety in the emergency room has been carried out following the patient safety SOP as much as possible. Keywords: Patient Safety, Nurse, Hospital ABSTRAK Keselamatan pasien (patient safety) didefinisikan sebagai layanan yang bertujuan untuk tidak menciderai dan merugikan pasien ataupun sebagai suatu sistem yang dimana rumah sakit membuat asuhan pasien lebih aman. Sasaran kepatuhan identifikasi pasien secara benar, komunikasi efektif dengan prosedur SBAR, kepatuhan petugas dalam menjaga kebersihan tangan, dan kepatuhan identifikasi pasien yang beresiko jatuh pencapaiannya masih berada dibawah 100%. Adapun tujuan dalam penelitian ini yaitu menganalisis Pelaksanaan Program Keselamatan Pasien IGD di RS Vina Estetika Medan Tahun 2021. Jenis penelitian ini yaitu menggunakan kalitatif deskrftif dengan sifat naturalistik. Data diperoleh melalui wawancara beberapa informan utama dan informan tambahan yaitu pasien IGD dengan metode Triangulasi dapat disimpulkan: Input (SDM, setiap perawat atau pelaksana di IGD sudah melakukan pelaksanaan keselamatan pasien dengan baik), Process (Keselamatan Pasien yang sudah dilakukan dengan sesuai SOP dengan menerapkan identifikasi pasien secara maksimal), Output (Pasien Ruang IGD, merasa sudah dilakukan identifikasi dengan baik). Keseimpulan dalam penelitian ini bahwa pelaksanaan safety patient di ruang IGD sudah terlaksana mengikuti SOP keselamatan pasien semaksimal mungkin. Kata Kunci: Keselamatan Pasien, Perawat, Rumah Sakit